2019
DOI: 10.1634/theoncologist.2019-0160
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Antibiotic Use Significantly Decreases Efficacy of Checkpoint Inhibitors in Patients with Advanced Cancer

Abstract: Background With the advent of immunotherapy, substantial progress has been made in improving outcomes for patients with advanced cancer. However, not all patients benefit equally from treatment, and confounding immune‐related issues may have an impact. Several studies suggest that antibiotic use (which alters the gut microbiome) may result in poorer outcomes for patients treated with immune checkpoint inhibitors (ICI). Materials and Methods This is a large, single‐site retrospective review of n = 291 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 38 publications
(45 reference statements)
4
99
0
4
Order By: Relevance
“…Other unique features of the iCCA microenvironment which could impact on responsiveness to ICIs include a tumour reactive stroma which can induce desmoplasia, limiting drug or immune cell penetration 47 ; the enterohepatic bile acid circulation which regulates hepatic natural killer T cell recruitment and interferon-gamma production 73 ; and frequent exposure to antibiotics owing to a propensity for biliary obstruction, which may modulate the gut microbiome and is associated with poorer outcomes on ICI therapy across tumour types. [74][75][76] Collectively, the heterogeneity of iCCA underscores the potential for differential responses to therapies targeting the immune system. Subanalyses of large cohorts of patients with CCA treated with ICIs are needed to identify the tumour and microenvironment factors associated with response and non-response.…”
Section: Tumour Immune Microenvironmentmentioning
confidence: 99%
“…Other unique features of the iCCA microenvironment which could impact on responsiveness to ICIs include a tumour reactive stroma which can induce desmoplasia, limiting drug or immune cell penetration 47 ; the enterohepatic bile acid circulation which regulates hepatic natural killer T cell recruitment and interferon-gamma production 73 ; and frequent exposure to antibiotics owing to a propensity for biliary obstruction, which may modulate the gut microbiome and is associated with poorer outcomes on ICI therapy across tumour types. [74][75][76] Collectively, the heterogeneity of iCCA underscores the potential for differential responses to therapies targeting the immune system. Subanalyses of large cohorts of patients with CCA treated with ICIs are needed to identify the tumour and microenvironment factors associated with response and non-response.…”
Section: Tumour Immune Microenvironmentmentioning
confidence: 99%
“…6 Similarly, several studies have shown that antibiotic use just before initiation and during immune checkpoint inhibitors (ICI) use was associated with shorter progression-free survival (PFS) and overall survival (OS) in patients with nonsmall cell lung cancer (NSCLC), renal cell cancer (RCC), urothelial cancer and melanoma. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In contrast to solid tumours treated with ICI, the success of cytotoxic chemotherapy in acute myeloid leukaemia (AML) depends on non-immune direct cytotoxicity, and thus, would not be expected to be changed by potential microbiota-mediated immune effects. However, the intestinal microbiota can modify antineoplastic effects of some chemotherapeutic agents.…”
Section: Key Questionsmentioning
confidence: 99%
“…After early encouraging reports showing that the use of anthracyclines such as doxorubicin, epirubicin or idarubicin to treat various tumor types resulted in the potentiation of the patient's anti-tumor immunity [133], and data from other studies showed that antibiotic treatment had no deleterious effects on the response of non-small cell lung carcinomas (NSCLC) to treatment with the immune checkpoint inhibitor (ICI) nivolumab [134,135], results from preclinical chemo-immunotherapy protocols combining cyclophosphamide chemotherapy with adoptive T-cell (ACT) immunotherapy, using a mouse model of B-cell lymphoma, demonstrated that prophylactic use of broad-spectrum antibiotics reduced the efficacy of cyclophosphamide and impaired the therapeutic effects of ACT [136]. Since then, most studies have reported negative effects of antibiotic exposure leading to diminished levels of efficacy of ICIs in immunotherapy protocols for the treatment of a variety of tumors, including lung tumors/NSCLC [137][138][139][140][141][142][143][144], advanced or metastatic renal cell carcinoma [137,141,142,144], urothelial carcinoma [141], and melanoma [141,143,144]. In addition, more recently, it has been reported that antibiotic use had a negative impact on the response of patients with locally advanced head-and-neck tumors to treatment protocols involving chemotherapy or radiotherapy [145].…”
Section: Antibiotics and Cancer Therapy Outcomesmentioning
confidence: 99%